Development of the innervation of the human inner ear. Issue 7 (13th November 2014) - Pechriggl, Elisabeth J.; Bitsche, Mario; Glueckert, Rudolf; Rask‐Andersen, Helge; Blumer, Michael J. F.; Schrott‐Fischer, Annelies; Fritsch, Helga
ABSTRACT Studies on the formation of neuronal structures of the human cochlea are rare, presumptively, due to the difficult accessibility of specimens, so that most investigations are performed on mouse models. By means of immunohistochemical and transmission electron microscopic techniques, we investigated an uninterrupted series of unique specimens from gestational week 8 to week 12. We were able to demonstrate the presence of nerve fibers in the prosensory domain at gestational week 8, followed by afferent synaptogenesis at week 11. We identified PAX2 as an early marker for hair cell differentiation. Glutamine synthetase‐positive peripheral glial cells occurred at the beginning of week 8. Transcription factor MAF B was used to demonstrate maturation of the spiral ganglion neurons. The early expression of tyrosine hydroxylase could be assessed. This study provides insights in the early assembly of the neural circuit and organization in humans. © 2014 Wiley Periodicals, Inc. Develop Neurobiol 75: 683–702, 2015